THE EFFECT OF USING YOUTUBE ON STUDENTS’ MOTIVATION IN LEARNING ENGLISH VOCABULARY - Megati Hia (Dialectical Literature and Educational Journal, 2021)
YouTube is an online media platform containing a variety of videos. It is also a place to post, share, and download videos. Its users range from children, teenagers, adults to parents, and no exception including students. This study aims to investigate the effect of using YouTube on students’ motivation in learning English vocabulary of the ninth grade at SMPN 35 Bekasi. A quantitative method was employed in this study involving 74 students from two groups – experimental class and control class. Data were obtained using questionnaires and interviews. Questionnaires were distributed to both groups and interviews were conducted in one group, i.e., experimental class. Data were calculated using the SPSS 22.00 computer program for the window. The results show that there was a significant effect of the use of YouTube on students’ motivation in learning English vocabulary in the ninth grade. The effect can be seen from the difference in the results of table of descriptive statistics with the mean value of the experimental class of 51.38 higher than that of the control class of 43.59 with each respondent (N) 37. The significant value of independent sample t-test calculated sig. (2-tailed).000 was < 0.05. This study indicates that the technique of using YouTube motivates students in learning English vocabulary.